Alice in Borderland. Volume 7 - Aso, Haro, 1980-; Werry, John (Translator) (Viz signature., 2023)
Most of the Face Card games continue to be a deadly challenge to Borderland's visitors, their often complicated or confusing rules meant to trick players into dooming themselves. In contrast, the King of Spades' game is refreshingly direct--kill or be killed! Can an uneasy coalition of visitors band together to take down the sniper King before his bullets declare game over for everyone?